PF.01 Prenatal Chromosomal Microarray Use: A Prospective Cohort of Fetuses and a Systematic Review and Meta-Analysis. (26th April 2013) - Hillman, SC; McMullan, DJ; Hall, G; Togneri, FS; James, N; Maher, EJ; Meller, CH; Williams, D; Wapner, RJ; Maher, ER; Kilby, MD
Abstract : Background: Chromosomal microarray testing (CMA) is utilised in prenatal diagnosis to detect chromosomal abnormalities not visible by full, conventional karyotyping. We present our prospective cohort of women undergoing fetal microarray and karyotyping for an abnormal prenatal ultrasound scan (USS). This cohort is presented in the context of a systematic review and meta-analysis of the literature (until December 2012) which defines overall detection rates by microarray over karyotyping. Systematic review methods: MEDLINE (1970–June 2012), EMBASE (1980–June 2012), Cinhal (1982–June 2012) were searched electronically. Selected studies had >5 cases and microarray testing was performed prenatally in addition to karyotyping. The search yielded 559 citations. Full manuscripts were retrieved for 85 and 24 primary studies were included in the systematic review. Cohort Methods: A prospective cohort study of 243 women undergoing microarray testing alongside karyotyping when a structural abnormality was detected on prenatal USS. Results: When clinical indication for testing was abnormal fetal USS our cohort study noted a 4.1% increase in detection rate; lower than the rate of 10.1% (95% CI 8.0–12.7%) by meta-analysis. When any clinical indication for prenatal microarray was meta-analysed the detection rate over karyotyping was 5.6% (95%CI 3.0–10.6%) and the variant of unknown significance (VOUS) rate was 1.4% (95%CI 0.5–3.7%). Conclusion: Chromosomal microarray is useful prenatally particularly for an abnormal fetal USS. Prospective counselling should include the approximate VOUS rate (1.4% rising to 2.1% for abnormal USS). It is likely that microarray testing will replace karyotyping in high risk pregnancies (such as abnormal USS).